2019
DOI: 10.1016/j.bbmt.2019.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation for Mucopolysaccharidoses: Past, Present, and Future

Abstract: Allogenic hematopoietic stem cell transplantation (HSCT) has proven to be a viable treatment option for a selected group of patients with mucopolysaccharidoses (MPS), including those with MPS types I, II, IVA, VI, and VII. Early diagnosis and timely referral to an expert in MPS are critical, followed by a complete examination and evaluation by a multidisciplinary team, including a transplantation physician. Treatment recommendations for MPS are based on multiple biological, sociological, and financial factors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
148
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 140 publications
(149 citation statements)
references
References 180 publications
(592 reference statements)
0
148
0
1
Order By: Relevance
“…Clinically, MPS IVA patients are characterized by short stature, corneal clouding, hypoplasia of the odontoid process, pectus carinatum, valvular heart disease, mild hepatomegaly, laxity of joints, kyphoscoliosis, and genu valgum without CNS impairment [81][82][83]. Treatment options for MPS IVA patients include non-steroidal anti-inflammatory drugs, antibiotics, oxygen supplementation, surgical procedures to correct orthopedic deformities and tracheal obstructions, ERT, and HSCT [81,82,84]. ERT has showed slight improvement in the 6-min walk test and the reduction of urinary KS [85], as well as an improvement in the maximal voluntary ventilation and performance of daily life activities [86].…”
Section: Mucopolysaccharidosis Type Ivamentioning
confidence: 99%
“…Clinically, MPS IVA patients are characterized by short stature, corneal clouding, hypoplasia of the odontoid process, pectus carinatum, valvular heart disease, mild hepatomegaly, laxity of joints, kyphoscoliosis, and genu valgum without CNS impairment [81][82][83]. Treatment options for MPS IVA patients include non-steroidal anti-inflammatory drugs, antibiotics, oxygen supplementation, surgical procedures to correct orthopedic deformities and tracheal obstructions, ERT, and HSCT [81,82,84]. ERT has showed slight improvement in the 6-min walk test and the reduction of urinary KS [85], as well as an improvement in the maximal voluntary ventilation and performance of daily life activities [86].…”
Section: Mucopolysaccharidosis Type Ivamentioning
confidence: 99%
“…[2][3][4] Treatment for MPSI is available through enzyme replacement therapy and stem cell transplantation. [5][6][7][8][9] It has consequently been suggested that this conditions is amenable to newborn screening (NBS). [5][6][7][8][9] NBS pilot studies have been initiated in the United States as well as other countries.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] It has consequently been suggested that this conditions is amenable to newborn screening (NBS). [5][6][7][8][9] NBS pilot studies have been initiated in the United States as well as other countries. 2,3 In addition, MPSI was added in 2016 to the recommended universal screening panel in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…ERT is routinely and successfully used in patients with several types of MPS [7]. ERT using a recombinant human GUS enzyme, vestronidase alfa, was approved by the FDA and EMA in 2019.…”
Section: Discussionmentioning
confidence: 99%
“…For ERT, a recombinant form of human GUS (vestronidase alpha) has been recently developed and used successfully [5], giving rise to a reduction of urinary GAGs and an improvement of the organomegaly [6]. However, the intravenously injected rhGUS does not cross the blood-brain-barrier and provides no effect on neurological signs, while HSCT can bring the enzyme into the brain via its secretion from donor-derived microglial cells and prevent or slow the neurological deterioration [7]. As learned from other MPS types, HSCT should be performed at an early stage of these diseases in the absence of pre-existing neurological damage.…”
Section: Introductionmentioning
confidence: 99%